Complementary and alternative medicine for the treatment of diabetes and associated complications: A review on therapeutic role of polyphenols - Preeti Sharma; Younis Ahmad Hajam; Rajesh Kumar; Seema Rai (Elsevier, 2022)
Background: Diabetes is one of the most challenging health problems in 21st century. It is a group of endocrine-metabolic disorder characterized by high glucose level (hyperglycemia) due to insufficient insulin secretion/action or both. It causes multi-organ failure viz hepatorenal damage, adult-onset blindness, lower-limb amputations, heart diseases and stroke, high blood pressure and nerve damage. Moreover, diabetic patients are having higher risk of cardiovascular complications including atherosclerosis, hypertension, lipoprotein abnormalities and cerebrovascular disease.Study design: Considering the potencies of currently available drugs for the treatment of diabetes and associated complications, present study was focussed to explore the role of plant bioactive components as alternative and easily accessible therapeutic remedies.Hypothesis/Purpose: This study the pooled status of diabetes, available treatments, attitude and traditional herbal polyphenols regarding diabetes.Results: This study was aimed to summarize the natural polyphenols having anti-diabetic, anti-inflammatory, anti-apoptotic and anti-cancerous activities. Polyphenols can decrease other metabolic diseases such as insulin resistance, hyperglycemia, hyperlipidemic, and obesity and Type-2 diabetes.Conclusion: Polyphenols are promising alternatives that can decrease the severity of diabetes and promote the other protective roles by decreasing the adverse effects of diabetes on other metabolic organs and their functions.